Plan de implementación del sistema de gestión de calidad basado en la NTC 6001:2017 en la empresa L. Servicio Eléctrico Industrial S.A.S. (2020)
This paper presents a plan for the implementation of the quality management system in L. Servicio Eléctrico Industrial SAS of the city of Bogotá DC based on the Colombian technical standard 6001: 2017, this standard was created by the ICONTEC for MiPymes (micro , small and medium enterprises) in a current business environment, based on the international standard ISO 9001: 2015. In principle, a diagnosis of the organization is made where the level of compliance of the organization is determined against the requirements of NTC 6001: 2017 and aspects to be strengthened in strategic planning, monitoring and process control were identified. Based on this information, an activity plan was structured in stages according to the PHVA cycle (plan, do, verify and act), and a schedule based on the requirements of the standard and the goals established for the implementation of the management system of quality.